2017
DOI: 10.34127/jrlab.v5i2.33
|View full text |Cite
|
Sign up to set email alerts
|

Pelaksanaan Pendidikan Soft Skills Pada Politeknik Lp3i Jakarta

Abstract: <p>Pendidikan Indonesia masih bertahan dan terjebak dengan gaya <em>hard skill</em>. Padahal nyaris setiap hari, iklan lowongan pekerjaan di media cetak maupun di internet  menggunakan kriteria-kriteria <em>soft skill</em> untuk merekrut pegawainya.  Realitas  inilah yang menjadikan pendidikan di Indonesia semakin memprihatinkan. Pengangguran terdidik membludak, padahal dunia industri kesulitan mencari pekerja “siap pakai” karena yang tersedia hanya para pencari kerja yang hanya s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
3
0
3
Order By: Relevance
“…Through the ro'isan system, individuals engage in communication, cooperation, and exposure to diverse perspectives from other organization members, serving as valuable learning resources. According to Dingot, as cited in (Hamonangan Ismail, 2017), team learning necessitates the following: 1) Cultivating communities of learners where relationships are consistently nurtured. 2) Valuing openness and diversity.…”
Section: Implementation Of Team Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Through the ro'isan system, individuals engage in communication, cooperation, and exposure to diverse perspectives from other organization members, serving as valuable learning resources. According to Dingot, as cited in (Hamonangan Ismail, 2017), team learning necessitates the following: 1) Cultivating communities of learners where relationships are consistently nurtured. 2) Valuing openness and diversity.…”
Section: Implementation Of Team Learningmentioning
confidence: 99%
“…This cohesion is fostered by honest and open communication among participants, as Dingot emphasizes the importance of team learning in his explanation. According to Dingot, as cited in Hamonangan Ismail (2017), team learning requires individuals to communicate candidly and openly, show mutual respect and appreciation, provide assessments while also seeking feedback, challenge each other to adopt new perspectives, adopt a holistic system approach, and authentically reveal themselves without masks. From the explanation above, it can be concluded that a Bahtsul Masa'il event necessitates solid teamwork.…”
Section: Implementation Of Team Learningmentioning
confidence: 99%
“…Sehingga point perilaku dan tingkahlaku ini menjadi hal utama yang juga harus di miliki didalam pengembangan soft skill. Selain itu rasa percaya diri juga harus dapat dimunculkan dan dibentuk melalui pembiasaan dan pelatihan (Ismail, 2017).…”
Section: Pendahuluanunclassified
“…Many research findings have shown that individual success in work is influenced by the individual's personality characteristics (Sutianah, Cucu, 2021: 157). Dingot Hamonangan Ismail (2016) defines soft skills as the abilities of an individual to interact with others (interpersonal skills) and manage oneself (intrapersonal skills) to maximize personal performance. Based on the above definition, it can be concluded that soft skills consist of two categories: interpersonal skills and intrapersonal skills.…”
Section: Definition Of Soft Skillsmentioning
confidence: 99%